2019
DOI: 10.1007/s42452-019-0540-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of geometrical parameters on heat and mass transfer processes in rotary heat exchangers

Abstract: This paper focuses on the influence of geometrical parameters of the rotary heat exchanger on its operation under highspeed rotor conditions. Proposed mathematical model of heat recovery wheel is based on a structure of the counter-flow heat exchanger model. After implementation of a numerical method on the modified α-model, the computer simulations were conducted. They allowed considering the distribution of the active heat and mass transfer zones ("dry," "wet" and "frost") on the matrix channel surface depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…The model is based on the original model of the counter-flow heat exchanger [10] and assumes non-oscillating mode of operation. A detailed description of the model was presented in our previous paper [15]. On this basis, a computer program was written to simulate the operation of the rotary heat exchanger.…”
Section: Analysis Of Creating Different Active Heat and Mass Transfermentioning
confidence: 99%
“…The model is based on the original model of the counter-flow heat exchanger [10] and assumes non-oscillating mode of operation. A detailed description of the model was presented in our previous paper [15]. On this basis, a computer program was written to simulate the operation of the rotary heat exchanger.…”
Section: Analysis Of Creating Different Active Heat and Mass Transfermentioning
confidence: 99%
“…Kanaś et al. 16 presented the influence of geometrical parameters on heat and mass transfer processes in rotary heat exchangers. They showed that the increase in the wheel’s depth leads to the increase in temperature effectiveness of heat recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of such recommendations has also been observed by RHE manufacturers [7]. In a study of geometrical parameters on heat and mass transfer processes [8], pressure drop over the RHE is used as an indicator of the frosting progress only; energy consumed by fans is not included in the evaluation. In some research projects, energy consumed in AHU fans is taken into account [9] and [10] and even is referred to as a "significant part" of the total primary energy used [10]; however, it still omitted from the overall energy efficiency evaluation.…”
Section: Introductionmentioning
confidence: 99%